Implementasi Model Double Track System: Sanksi Pidana dan Tindakan sebagai Sistem Pemidanaan terhadap Pelaku Tindak Pidana Penyalahgunaan Narkotika di Lembaga Pemasyarakatan Kelas II A Kabupaten Langkat - Sri Sulistyawati; Iwan Setiawan; Bambang Hermanto (Universitas Medan Area, 2020)
Narcotics abuse is a danger that can destroy the next generation and hinder the development of the Indonesian nation in carrying out development in every sector of life. The narcotics problem is very much a concern of the people of Indonesia and especially the Province of North Sumatra because this province is ranked second after the Special Capital Region of Jakarta in the number of narcotics users. This research is very important in order to help the government program in order to avoid the youth of the nation's successors of narcotics users and provide a deterrent effect to the perpetrators of criminal acts of narcotics abuse. That the application of Law No. 35 of 2009 concerning narcotics has set about a double track system where narcotics addicts can be punished with actions in the form of rehabilitation. But in its application the judge always imposes criminal sanctions in the form of prison for drug addicts. So that more and more drug addicts in prison. The problems discussed in this study are the implementation of the double track system model, criminal sanctions and actions as a criminal system for the perpetrators of narcotics abuse crimes in Langkat Class II Penitentiary, whether this double track system can be implemented and whatever is an obstacle in the implementation of this double track system, by using the socio-legal research approach. Conclusions from the results of the study up to now the criminal system that was handed down in the Langkat District Court against narcotics criminals still used a single track system, so that all prisoners who served their sentences in Class II A Narcotics Lap Langkat were sentenced in the form of imprisonment.